Challenges for Romanian Higher Education - Deca, Ligia (International Higher Education, 2015)
As one of the most recent EU and NATO members, Romania has transitioned through 25 years of democratic reforms, including in higher education. The internationalization of higher education has meant an opportunity for reform, but in light of current challenges – demographic downturn, inequality and lack of funding – the tendency of decision-makers to use a double discourse in relation to domestic and international actors endangers the future of Romanian universities. The article explores the current challenges and points to the discrepancies between current policies and obvious higher education problems.